Glycyphagus domesticus - Cilbircioğlu, Cihan; Çobanoğlu, Sultan (Zenodo, 2019)
{"references": ["Goracci, E, Lazzeri S, Zuccherelli, D, Rossetti, M. & Poggianti, AM. (1985) Acari of food storage facilities: An ecologic and immuno-allergic study. Quad Sclavo Diagn, 21 (4): 436 - 46 (In Italian).", "Gulegen, E, Girisgin, O., Kutukoglu, F., Girisgin, A. O. & Coskun, SZ. (2005) Mite species found in house dust in houses in Bursa. Turkiye Parazitoloji Dergisi, 29 (3): 185 - 187.", "Cobanoglu, S. (1996) Typhloctonus Muma, 1961 (Acarina: Phytoseiidae) species, from thrace of Turkey. Doga, Turk Tarim ve Ormancilik Dergisi, 20: 353 - 357.", "Medeni, A., Erman, O. K., Dogan, S. & Ayyildiz, N. (2013) Bitlis ve Mus illeri ev tozu akarlari. Turkiye Entomoloji Bulteni, 3 (3): 169 - 177.", "Akdemir, C. & Gurdal, H. (2005) House dust mite in Kutahya, Turkey. Turkiye Parazitoloji Dergisi, 29 (2): 110 - 115 (In Turkish)."]}

Glycyphagus domesticus (De Geer, 1778) Width: 260.82 ± 0.45 (202.20–350.10), length: 395.44 ± 0.45 (321.48–456.32) (n = 10). Specimens examined Taşköprü / Ağcıkişi Village garlic storage. 26.I.2015 (2 ♀♀, 2 ♂♂); Hanönü/ İncesu Village. 26.IV.2015 (1 ♂). Comments This mite is called furniture mite, cereal mite or household mite (Goracci et al. 1985). This species was reported in Bursa (Gülegen et al. 2005), on storage products in Edirne (Çobanoğlu 1996), as house dust mite in Bitlis and Muş (Medeni et al. 2013) and Kutahya (Akdemir and Gürdal 2005).

Published as part of Cilbircioğlu, Cihan & Çobanoğlu, Sultan, 2019, Phytophagous mite (Acari) species on garlic (Allium sativum L.) cultivation areas and storages of Kastamonu, Turkey, pp. 211-224 in Persian Journal of Acarology 8 (3) on page 219, DOI: 10.22073/pja.v8i3.46349, http://zenodo.org/record/7173998
Keywords: Arthropoda; Glycyphagidae; Arachnida; Animalia; Glycyphagus; Biodiversity; Glycyphagus domesticus; Sarcoptiformes; Taxonomy; 2. Zero hunger